Surface Degradation Analysis Of Roller Bearing - Yusof, Nurul Farhana Mohd (2012)
Surface degradation analysis and defects detection of roller bearing are crucial for the prediction of the impending failure in machineries. In this work, two conditions of grease lubrication and unlubricated condition are investigated. The analysis is focused on the surface degradation of the inner race and the rolling element since these surfaces suffer from the higher contact stress level. The natural surface degradation of the roller bearing is monitored from the beginning of the experiment until damage. The lubrication film thickness is determined by the Hamrock-Dowson equation which showed that the grease lubricated bearing operated under the elastrohydrodynamic lubrication, with the ratio of lubrication film thickness to the surface roughness of λ in the range of 0.9 to 3.65. The unlubricated bearing was damaged after 20 minutes whereas the grease lubricated bearing continued to operate for 6600 minutes. The observation under microscope showed that the surface underwent smoothening process where the surface roughness decreases during the running-in state with the λ = 3.65 to 2.3 followed by roughening at the steady state where the surface roughness increases, with λ = 2.3 to 0.9. At damage, the value of λ = 0.9 can be associated with the high level of the bearing vibration. The increase of vibration level becomes rapid at the critical value of λ = 1.6. As such the overall vibration level of the bearing can be related to the surface degradation. For unlubricated condition, these processes took place faster. Both waviness and roundness measurement showed higher form change of the inner race. Envelope analysis at the end of experiment showed that the bearing damaged can be traced at the inner race with the clear peak of the inner race bearing defect frequency.